PENGARUH BUDGETARY GOAL CHARACTERISTICS TERHADAP KINERJA MANAJERIAL PADA RUMAH SAKIT PEMERINTAH DI KOTA DENPASAR - MAS MAY MURTHI, IDA AYU; SUJANA, I KETUT (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 4 No 2 (2009), 2009)
Managerial performance can be evaluated based onbudgetary goal characteristics (BGC). The aims of this study are tofind evidences about association between BGC and managerialperformance, and to investigate the effect of paternalistic culture andorganization commitment on the relationship between BGC andmanagerial performance. Respondents include parties thatparticipate in the process of budget arrangement. This study usessimple regression analysis and moderated regression analysis.Results show that BGC do not affect managerial performance, whilethe moderating variables, both paternalistic culture and organizationcommitment, have moderating effect to the relation of BGC andmanagerial performance.
Keywords: budgetary goal, performance, paternalistic, commitment